Determinants of Full - Time Teachers's Job Duration at Private High Schools in Ho Chi Minh City - Nguyễn Nguyên Bằng; Nguyễn Minh Hà; Lê Khoa Huân (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2020)
This study’s o jectives are to identify determinants of full time teachers’ jo duration at private high schools in Ho Chi Minh City and to suggest policy implications to last full time teachers’ job duration for improving the educational quality of the high school level. The study uses the data of surveying directly 147 teachers working for the private high schools in Ho Chi Minh city and applies OLS regression. The findings are that 10 factors influencing to teachers’ jo durations are ( ) teacher’ age, (2) techer’s gender, (3) marriage status, ( ) salary, (5) enefit, (6) teachers’ education, ( ) num er of techters in high school, (8) school’ facilities, (9) leadership in school, and (10) working conditions.